BENTUK PENYAJIAN TARI TANGAN DALAM PESTA PERKAWINAN DI KECAMATAN LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Musty, Enjelina; Desfiarni (Universitas Negeri Padang, 2026)
This study aims to describe and analyze the presentation of the Hand Dance in a wedding party in Linggo Sari Baganti District, Pesisir Selatan Regency. This type of research is qualitative research with a descriptive approach. The research instrument is the researcher himself and assisted by stationery and a camera. Data was collected through literature studies, observation, interviews and documentation. Data analysis techniques are data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the presentation of the Hand Dance in a wedding party not only reveals the aesthetic and technical aspects of the dance but also reflects its important role in the social and cultural structure of the Linggo Sari Baganti District, Pesisir Selatan Regency. The Hand Dance movements depict the flexibility and dynamics of the body, with the names of the movements Pasambahan, Pilinkirok Tangan, Kirok Alang Tabang Manjalang Gunuang, to Hentak Gajah Babunyi, which show the symbolic richness and beauty of the dance. This dance is performed by two male dancers, aged 10 to 75. Within the context of wedding ceremonies, the Hand Dance serves as entertainment. The existence and continuity of the Hand Dance demonstrate the importance of preserving traditional arts as a cultural identity passed down from generation to generation and demonstrates that art can adapt and survive in modern society.